Sanitary status of public school food services in Maceió (Alagoas, Brazil), 2013 | Aspectos higiênico-sanitários dos serviços de alimentação das escolas públicas de Maceió, 2013 - Taciana Gissely da Silva Rebelo; Maria Cristina Delgado da Silva; Haroldo da Silva Ferreira (Fundação Oswaldo Cruz (FIOCRUZ), 2015)
The risk of foodborne illnesses is related to incorrect food handling practices and food service infrastructure and equipment. This study aimed to assess the sanitary status of the food services of public schools in Maceió. The services of 40 of 121 schools were chosen by simple random sampling. The assessment used a good-practices checklist containing all of the rules in Resolution 216/04 of the National Sanitary Surveillance Agency. The possible answers were "in compliance" and "not in compliance," which were then considered to determine the compliance of the service with the above-mentioned Resolution. The services were classified as: critical (≤ 30%), unsatisfactory (31 to 49%), regular (50 to 69%), satisfactory (70 to 89%), and excellent (≥ 90%). Not one service achieved regular, satisfactory, or excellent compliance; 23 (57.5%) and 17 (42.5%) presented with unsatisfactory and critical compliance, respectively. The main problems were bad infrastructure and poor food-handling practices. The services do not comply with the norms for safe food production. This situation demands urgent action from the professionals and managers responsible for school meals, nutrition, and student health in the capital of Alagoas. ---------------------------------------------------------------------------------------------- Objetivou-se avaliar os aspectos higiênico-sanitários dos serviços de alimentação dos estabelecimentos públicos de ensino fundamental de Maceió, Estado de Alagoas, Brasil. De um total de 121 escolas, 40 foram selecionadas por sorteio simples e tiveram seus serviços avaliados. Para isso, utilizou-se um checklist de boas práticas baseado na Resolução 216/04 da Agência Nacional de Vigilância Sanitária, constando 83 questões referentes aos aspectos higiênico-sanitários, cujas respostas, "conforme" ou "não conforme", determinam o percentual de adequação do serviço. De acordo com este percentual, os serviços foram classificados nas seguintes categorias: crítico (≤ 30%), insatisfatório (31 a 49%), regular (50 a 69%), satisfatório (70 a 89%) e excelente (≥ 90%). Nenhum serviço atingiu a condição de regular, satisfatório ou excelente, sendo que 23 (57,5%) serviços apresentaram nível insatisfatório e 17 (42,5%) nível crítico. As principais inconformidades relacionaram-se às condições de infraestrutura e à baixa qualificação dos funcionários no que se refere às boas práticas de manipulação de alimentos. Os serviços estudados não atendem às normas de produção de alimento seguro, situação que constitui uma violação ao direito humano à alimentação adequada e demanda providências urgentes por parte dos profissionais e gestores envolvidos com a alimentação, nutrição e com a saúde dos escolares da capital alagoana.